Exposure to family violence from childhood to adulthood - Margot Shields; Lil Tonmyr; Wendy E. Hovdestad; Andrea Gonzalez; Harriet MacMillan (BMC, 2020)
Abstract Background Both childhood maltreatment (CM) and intimate partner violence (IPV) are public health problems that have been related to a wide range of adverse health consequences. However, studies examining associations between specific types of CM and experiencing IPV in adulthood have yielded conflicting results. Methods Using data from 10,608 men and 11,458 women aged 18 or older from Canada's 2014 General Social Survey, we examined associations between three types of CM-childhood physical abuse (CPA), childhood sexual abuse (CSA), and childhood exposure to IPV -and subsequent intimate partner violence (IPV) in adulthood (physical, sexual or emotional). Results When potential confounders were controlled, CPA, CSA and childhood exposure to IPV were associated with IPV in adulthood for both sexes (odds ratios, 1.7, 1.8 and 2.0 for men, and 2.2, 2.0 and 2.1 for women). When severity and frequency of CM were examined, a dose-response relationship between all three types of CM and IPV in adulthood was observed among women (meaning that as the severity/frequency of CM increased, the likelihood of reporting IPV also increased); among men, a dose-response relationship was observed only for CPA. Conclusions The association between CM and IPV in adulthood is particularly concerning because experiencing multiple forms of trauma has cumulative effects. Lifespan studies have shown that individuals who experience multiple incidents of abuse exhibit the highest levels of impairment. This underscores the importance of programs to eradicate both CM and IPV. This underscores the importance of programs to eradicate both CM and IPV. Future research should focus on assessing interventions designed to promote healthy relationships and the provision of emotional support and coping mechanisms to children and families in abusive situations.